Jordan a Hashemite legacy - Milton-Edwards, Beverley (Contemporary Middle East, 2003)
Created as a mechanism for maintaining British influence through a local patron, Jordan's future never looked certain. Nevertheless, under the leadership of the Hashemite monarchy led by Abdullah, and then by his grandson Hussein, the Kingdom of Jordan has become a permanent feature of the modern Middle East. This volume, intended for both academic and general readers, offers an overview of the history, politics and economics of this fascinating country and its role in a region disfigured by the Arab-Israeli conflict. The main focus of the book is on King Hussein's reign, his internal struggle with the Palestinians, his quest to modernise his kingdom and his pursuit of an agenda for peace inclusive of Israel and Iraq. The authors also consider the prospects for the 'new Jordan' under King Abdullah II.